2008
DOI: 10.3928/00989134-20080601-06
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and the Sleep Environment of Older Adults in Acute Care Settings

Abstract: The purpose of this descriptive pilot study was to describe sleep characteristics of hospitalized older adults and the nighttime environmental noise and light they encountered. Study participants included patients in an acute care setting; actigraphy and light and sound meters were used to measure the variables. Mean sleep time was 215 minutes, and the average sleep efficiency was 44.72%. Nighttime sleep was fragmented into 5 to 38 intervals of 15 to 24 minutes, with frequent awakenings. Mean light levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…8 A lack of sleep has also been associated with, but is not necessarily the cause of, ICU delirium. 32 Recently, Bartick et al 33 reported that decreasing sleep disruptions by lowering lighting levels, having nurses avoid waking patients for measurement of vital signs, and instigating a "quiet time" resulted in decreased use of sedatives among patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 A lack of sleep has also been associated with, but is not necessarily the cause of, ICU delirium. 32 Recently, Bartick et al 33 reported that decreasing sleep disruptions by lowering lighting levels, having nurses avoid waking patients for measurement of vital signs, and instigating a "quiet time" resulted in decreased use of sedatives among patients.…”
mentioning
confidence: 99%
“…As a reference, 60 dB(A) is about the S leep disruption in intensive care units (ICUs) is common 1 and is detrimental to patients' health and recovery. 2 Causes of the disruptions include necessary medical interventions, such as measurement of vital signs and checking of equipment 3 ; disruptions due to pain, medications, and stress 4,5 ; staff interactions with other patients and one another 6,7 ; environmental light 8 ; and noise. [9][10][11] In a review of the literature, Xie et al 12 reported that between 17% and 57.6% of arousals and awakenings are due to noise.…”
mentioning
confidence: 99%
“…29 Abnormal light exposure likely explains the disruption in circadian rhythms seen in hospitalized or perioperative patients. 30 Bright light is the strongest time giver that entrains the endogenous circadian rhythm to the external environment. Bright light directly suppresses melatonin and can alter circadian rhythms depending on the exposure time (a delay in circadian phase when bright light exposure occurs during the beginning of the biological night and an advance in circadian phase when the exposure occurs in the morning).…”
Section: Immobilitymentioning
confidence: 99%
“…14,17 Natural light, particularly when accompanied by views of the outdoors, reduces staff fatigue, a causative factor in medical errors. 15,19 Sound absorbing surfaces such as acoustical tiles or carpet can promote rest by lessening the transmission of noise occurring both inside and outside of the room. 15,19 Sound absorbing surfaces such as acoustical tiles or carpet can promote rest by lessening the transmission of noise occurring both inside and outside of the room.…”
Section: Review Of Evidencementioning
confidence: 99%